ANALISA KINERJA RUAS JALAN TUANKU TAMBUSAI (KUMU) PASIR PENGARAIAN PADA KONDISI PUNCAK - Pada Lumba; Heffi Christya Rahayu (Universitas Pasir Pengaraian, 2011)
Every day fenomena at Tuanku Tambusai Street (Kumu), there some public transport still take or drop passanger at the unsafe place, that, while the road capasity is decrease, this can be disturbing the other vehycle that trought that road. Beside that the survey at buzy road, there are shop, campus and other lokation that can create high traffic rise and pull. To solve this problem, have to analize the condition of the road now and 5 year later, is the road capacity still under the alowed tolerance or it’s execceded.This research used Survey Method, that put some surveyor at road that want to survey to count vehicle that trought the road in 1 hour, with 5 minuttes interval. From the data obtained and analyzed primarily related to the performance of the road on existing condition and the next 5 years.From the analysis, where the value of the degree of saturation at 0.24 which is still far from the value of tolerance limits required by MKJI 1997. So for the current conditions of road are still able to accommodate traffic flow that occurs.